2023
DOI: 10.3390/molecules28020510
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Helicene Type Hole-Transporting Materials for Perovskite Solar Cells

Abstract: Perovskite solar cells have emerged as one of the most promising photovoltaic technologies for future clean energy sources to replace fossil fuels. Among the various components in a perovskite solar cell, the hole-transporting materials play significant roles in boosting device performance and stability. Recently, hole-transporting materials with helicene cores have received much attention due to their unique properties and ability to improve the performance and stability of the perovskite solar cells. The foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 42 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…The binding of n‐helicene‐diamine to double‐strand DNA was also reported earlier, in 2002, by Honzawa et al [14] . Studies have also shown that n‐helicene based hole‐transporting materials can be used for improving the stability of perovskite solar cells [15–19] . Shi et al .…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…The binding of n‐helicene‐diamine to double‐strand DNA was also reported earlier, in 2002, by Honzawa et al [14] . Studies have also shown that n‐helicene based hole‐transporting materials can be used for improving the stability of perovskite solar cells [15–19] . Shi et al .…”
Section: Introductionsupporting
confidence: 58%
“…The binding of n-helicene-diamine to doublestrand DNA was also reported earlier, in 2002, by Honzawa et al [14] Studies have also shown that n-helicene based holetransporting materials can be used for improving the stability of perovskite solar cells. [15][16][17][18][19] Shi et al have reported that a nonplanar-fused structure like 7-helicene derivative prevents the close-packing of molecules in the solid state and keep the molecule in a good amorphous state, which allowed the optimization of the properties of OLED. [3] Lately, there has been significant research interest in materials exhibiting substantial two-photon absorption (TPA), a second-order non-linear optical (NLO) property.…”
Section: Introductionmentioning
confidence: 99%
“…Although the first successful synthesis of helicene was reported by Meisenheimer and Witte long ago in 1903, [42] they have emerged for the PSCs until a few years ago. [43] More than curved structure, the most special of helicene is the screw-shaped skeleton as its name implies, allowing the molecule to exhibit chiral forms without asymmetric carbons and chiral centers. [44] Generally, as shown in Figure 1, helicene can be a good πelectron donor similar to most π-conjugated compounds but shows a greater departure from planarity, which delivers a peculiar molecular packing mode and intermolecular interacting situation, and thereby affecting the charge carrier dynamics.…”
Section: Helicenesmentioning
confidence: 99%
“…Considering the strong electron-donating nature of thiophene unit, researchers preferred to adopt the Dπ-D idea for molecular design with the purpose of obtaining a stronger hole transport ability. [43] Follow this idea, Wang et al developed an intriguing helical D-π-D molecule, T5H-OMeDPA (Figure 4d), exhibiting a hole mobility that was three times higher than that of its planar analogue. [53] Accordingly, due to the reduced hole transport resistance, the T5H-OMeDPA-based device delivered a champion PCE of 21.1 %, which was higher than either the planar analogue (19.8 %) or the spiro-OMeTAD (20.6 %).…”
Section: Helicenesmentioning
confidence: 99%
“…34–36 Vailassery and Sun made a detailed review on the properties and device performance of helicene-based organic semiconductors for perovskite solar cells. 37 Density functional theory calculations reveal that J4 (Fig. 1), featuring aza[5]helicene as the π-linker, exhibits a theoretical HOMO energy level of −4.79 eV, comparable to spiro-OMeTAD (−4.74 eV), while counterparts with oxa[5]helicene and thia[5]helicene display deeper HOMOs (−4.91 eV and −4.90 eV, respectively).…”
Section: Introductionmentioning
confidence: 99%